Analisis kesalahan siswa dalam penyelesaian soal perbandingan trigonometri segitiga siku-siku berdasarkan kriteria watson - Bayu, Cindivia Putri; Yohanie, Dian Devita; Handayani, Aprilia Dwi (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2021)
This study aims to analyze the location of students' errors in problem solving and the causal factors based on Watson's criteria. This type of qualitative descriptive research, with the subject of three students of class X AKL 1 taken based on certain considerations according to the criteria or can be called purposive sampling technique. Data collection techniques include direct observation in schools, interviews with subjects and documentation. Triangulation techniques used for data analysis include data reduction, presentation and conclusion drawing. From the results of the analysis, it was found that four types of errors were located inimproper procedures, indirect manipulation, missing data and missing conclusions. The cause of the error is students lack understanding of material concepts, being careless in reading questions, forgetting formulas, being in a hurry, and new factors are found, namely students use other paper to write down the completion steps. The results of the study can explain in detail the errors made by students in solving problems, so that it can minimize the occurrence of similar errors and improve the learning process of mathematics.